DEVELOPMENT OF ENZYME-LINKAGE IMMUNOSORBENT ASSAY AGAINST TYPE B OF CLOSTRIDIUM BOTULINUM: A PRELIMINARY STUDY - Depamede, S.N.; Kisworo, D. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
Clostridium botulinum neurotoxin (BoNTs) is one of the causes of economic loss in the livestockindustry. This economic loss would be as a direct result when animals poisoned by BoNTs or indirectlywhen the livestock products are contaminated by BoNTs, which end up with the products are banned byauthority. Therefore a routine surveillance of BoNTs in the farm and in livestock product processingindustry is urgently needed. One of the most relatively quick and accurate methods to perform a routinedetection of the presence of BoNTs is enzyme-linkage immunosorbant assay (ELISA). In this article wedescribe the results of the development of ELISA, using polyclonal antibodies against BoNTs-Bproduced locally. Antibodies were generated from six Balb/c mice with standard immunologicalmethods. Mice were immunized three times for a period of 8 weeks with a commercial type BClostridium botulinum toxoid at a dose of 100 ng per mouse per injection. The resulting antibody waspurified by a combination of ammonium sulfate precipitation 50% (w/v) technique and a protein Acolumn method. The results of this preliminary study indicated that the developed ELISA methodcapable of detecting type B Clostridium botulinum toxin up to 1.0 ng/ml.